Kinship of bidayuh dayak ethnic at the border of Entikong-Indonesia and Tebedu-Malaysia - Efriani, Efriani; Hasanah, Hasanah; Bayuardi, Galuh (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
This study of Dayak Bidayuh ethnic kinship system at the boundaries of Entikong and Tebedu is based on the issue of border area development, the issue of cultural extinction and cultural values, as well as the issue of cultural claims and cultural values. Besides, the existence of Bidayuh ethnic groups spread across Indonesia and Malaysia has become interesting to study and describe. The study used qualitative method by interviewing and observing people of Dayak Bidayuh in Sontas-Indonesia and Bidayauh in Entubuh-Malaysia. Based on the concept of kinship and border studies, this study shows that (1) Bidayuh Sontas Kinship System refers to the concept of kinship system with a unilateral lineage pattern, so that the Bidayuh Sontas nuclear family is part of an extended family; (2) Bidayuh Sontas has a transnational kinship pattern with Entubuh-Malaysia Bidayuh; (3) The presence of the State is the cause of the separation of Bidayuh Sontas citizenship from Bidayuh Entubuh; (4) When there is a marriage between them, the citizenship must be determined; and (5) Transnational kinship Bidayuh at the Entikong-Indonesia and Tebedu-Malaysia Border as a socio-cultural space phenomenon. An ethnic community that existed before the presence of state’s border is still continuing their daily lives, even though they have been constructed into different nationalities.